Research and Characteristic Analysis of A New Type of Dual Winding Electromagnetic Brake - Liu, Tongliang; Sun, Shida (International Journal of Mechanical and Electrical Engineering, 2024)
Taking the electromagnetic brake as the research object, a new structure of double-winding electromagnetic brake is proposed in view of the serious temperature rise phenomenon of traditional single-winding electromagnetic brake, the high requirement of insulation level and the obvious decrease of electromagnetic force. The equivalent magnetic circuit method is used to analyze and calculate the magnetic field, and the simulation model of the new brake is constructed, and the influence of different parameters on the braking characteristics of the double-winding electromagnetic brake is analyzed by the single-variable method, and the influence curves of each parameter on the electromagnetic force and response time are obtained. At the same time, the magnetic-thermal coupling analysis of the double-winding electromagnetic brake is carried out, and the results show that the total ampere-turns and power of the double-winding electromagnetic brake decreases by 15.3% in the same proportion, the rated electromagnetic force decreases by 22.9%, the release time grows by 23.7%, and the closure time is shortened by 14.6%.